2001
DOI: 10.1006/bijl.2000.0504
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in steppe tortoises (Testudo horsfieldii): influence of the environment and sexual selection on body shape and mobility

Abstract: Selective forces shape sexes differently, with male body proportions facing strong selection to enhance mate searching and male-to-male combat traits, and female fitness being influenced by the ability to assimilate large amounts of nutrients necessary for vitellogenesis (and/or gestation), and their ability to carry the eggs or embryos. We evaluated the sexual dimorphism of body proportion of more than 800 wild steppe tortoises (Testudo horsfieldii) in Uzbekistan. The thick, well-developed shell offers protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(129 citation statements)
references
References 22 publications
5
123
1
Order By: Relevance
“…When tested regardless of body size, only few morphological traits (MaxCW, ANW and ASJ) had an effect on male RT. This result came as a surprise since some morphological traits, such as bridge length and shell height, were previously recognized to have an effect on self-righting (Bonnet et al 2001;Zuffi and Plaitano 2007;Golubović et al 2013a) but were not confirmed by this study.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…When tested regardless of body size, only few morphological traits (MaxCW, ANW and ASJ) had an effect on male RT. This result came as a surprise since some morphological traits, such as bridge length and shell height, were previously recognized to have an effect on self-righting (Bonnet et al 2001;Zuffi and Plaitano 2007;Golubović et al 2013a) but were not confirmed by this study.…”
Section: Discussioncontrasting
confidence: 86%
“…Males can also lose their equilibrium while mounting a female or during combats with rivals, which consequently can result with better self-righting performances in males (Bonnet et al 2001;Golubović et al 2013a). Overturned on their backs, tortoises are not able to quickly escape, since they have to go through a self-righting process first.…”
Section: Behavioural Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both righting behaviour (Ashe 1970;Wassersug & Izumi-Kurotani 1993;Rivera et al 2004;Stancher et al 2006) and the evolution of shell morphology (Rouault & Blanc 1978;Claude et al 2003;Myers et al 2006) of turtles have been studied recently. An example of their interaction is the sexual dimorphism of species where males are often overturned during combats (Bonnet et al 2001;Willemsen & Hailey 2003;Mann et al 2006), and their shell has adapted to facilitate righting. Here we develop a geometric shell model based on field data to uncover systematically the connections between righting strategies and turtle shell morphology.…”
Section: Introductionmentioning
confidence: 99%